Tourism in the Himalayas: A Study of the Landscape of Mardi Himal Trekking Route, Kaski District, Nepal - Poudel, Khagendra Raj; Paudel, Naresh (The Himalayan Geographers, 2024)
This article examines how tourism affects the natural environment and local people along the Mardi Himal Trek in Kaski District, Nepal. The research was based on surveys, GPS mapping, and interviews with 21 local people, including villagers, hotel owners, guides, and tourists. The findings show both advantages and problems related to the growth of tourism. Around 85% of participants said tourism was a key source of income, and 60% noted clear improvements in their household income and infrastructure. However, 70% also noticed changes in cultural behavior. Environmental issues like trail erosion, deforestation, and waste disposal are still serious. The trail varied scenery from forests to high mountain ridges and cultural features like prayer flags and village homestays continue to attract visitors from Nepal and abroad. As more people visit the area, careful planning is needed to protect its environment and culture, while also helping local people.